2022
DOI: 10.1021/acs.jpcc.2c02729
|View full text |Cite
|
Sign up to set email alerts
|

Transition from Capacitive to Inductive Hysteresis: A Neuron-Style Model to Correlate IV Curves to Impedances of Metal Halide Perovskites

Abstract: Metal halide perovskite (MHP) devices often show different types of hysteresis in separate voltage domains. At low voltage, the impedance response is capacitive, and the cell gives regular hysteresis. At high voltage, the hysteresis is inverted, corresponding to an inductive response that causes a negative capacitance feature. We calculate the hysteresis current due to a chemical inductor model, and we show that the current is inversely proportional to the voltage scan rate. We formulate a general dynamical mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
85
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 52 publications
(88 citation statements)
references
References 109 publications
(226 reference statements)
3
85
0
Order By: Relevance
“…An early round of studies attributed this feature to accumulation of electronic charge at the interfaces. 19,20 A subset of lower frequency capacitance is called inductance (otherwise known as negative capacitance) [21][22][23][24] which appears as a hook or a loop in the Nyquist plot representation of EIS measurements and is believed to be detrimental to PSC performance. 25 Inductance has been interpreted in various ways in the literature such as the emptying rate of an intermediate state 19 and interfacial charge transfer resistance.…”
Section: Introductionmentioning
confidence: 99%
“…An early round of studies attributed this feature to accumulation of electronic charge at the interfaces. 19,20 A subset of lower frequency capacitance is called inductance (otherwise known as negative capacitance) [21][22][23][24] which appears as a hook or a loop in the Nyquist plot representation of EIS measurements and is believed to be detrimental to PSC performance. 25 Inductance has been interpreted in various ways in the literature such as the emptying rate of an intermediate state 19 and interfacial charge transfer resistance.…”
Section: Introductionmentioning
confidence: 99%
“…The problem is that many interpretations are based on apparently different models. A connection has been established between the type of hysteresis and the dominant features in the equivalent circuit of impedance spectroscopy. , This is also a matter of general interest since the inductive hysteresis turns out to be related to the famous negative capacitance widely observed across different disciplines . It is suggested that a stabilized negative capacitance holds the key for future generations of low consumption microelectronics. , …”
mentioning
confidence: 99%
“…The contact impedance contains a surface capacitance C 1 , a resistance R 1 , and a chemical inductor structure [ 60 ] composed of the resistance R a and inductor L a . [ 59,61 ] Therefore, the contact impedance is: Zcbadbreak=(iC1ω + 1R1+1Rnormala(1+iω/ωnormala))1\[{Z_{\rm{c}}} = {\left( {i{C_1}\omega \; + \;\frac{1}{{{R_1}}} + \frac{1}{{{R_{\rm{a}}}\left( {1 + i\omega /{\omega _{\rm{a}}}} \right)}}} \right)^{ - 1}}\] where ω a is the characteristic frequency of the contact chemical inductor. The bulk impedance is: Zbbadbreak=(Cµiω+1Rnr+1Zrad) 1\[{Z_{\rm{b}}} = {\left( {{C_\mu }i\omega + \frac{1}{{{R_{{\rm{nr}}}}}} + \frac{1}{{{Z_{{\rm{rad}}}}}}} \right)^{\; - 1}}\] and the radiative impedance has the expression: Zradbadbreak=Rrad(1badbreak+τdiω)\[{Z_{{\rm{rad}}}} = {R_{{\rm{rad}}}}\left( {1 + {\tau _{\rm{d}}}i\omega } \right)\] …”
Section: Theory Of Light Emission Voltage‐modulated Spectroscopymentioning
confidence: 99%
“…The contact impedance contains a surface capacitance C 1 , a resistance R 1 , and a chemical inductor structure [60] composed of the resistance R a and inductor L a . [59,61] Therefore, the contact impedance is:…”
Section: Theory Of Light Emission Voltage-modulated Spectroscopymentioning
confidence: 99%
See 1 more Smart Citation